PENGARUH ROTASI DAN MUTASI KERJA TERHADAP KINERJA KARYAWAN PTPN 7 CABANG BENGKULU - Sari, Maya; Onsardi, Onsardi; Arianto, Tezar (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2020)
This study aimed to determine the Effect of Rotation and work Mutation on employee performance ( A Case Study On Employees of PTPN 7 Bengkulu ). This research method was quantitative with a population of 40 people while the study sample was taken by using the formula of total sampling technique. The data collection technique used observation and questionnaire with the research variables were Rotation (X1),Work Mutation (X2), and Employee Performance (Y), the result of multiple linear equation Y = 5.760 + 0.735 ( X_1 ) + 0.590 ( X_2 ). Hypothesis test results of work rotation variable (X1), and work Mutation (X2) F Test Result Obtained Fsig 97, 185 and a significant value (sig) of 0,000 result can be interpreted as a significant value of 0,000 <0.050 that H3 is accepted means that simultaneously rotational and mutation variables of work has a significant effect to ward Employees’ performance of PTPN 7 Bengkulu. The result of t count Rotation variable (X1) was 5.626 and significant value (sig) 0.000 means 0.000 <0.050 and the working mutation variable (X2) was 2.485 and significant value (sig) 0.018 <0.050 then the ha hypothesis is accepted. In other words that rotation and work mutation was significantly influence’ performance of PTPN 7 Bengkulu.